USE OF EVODIAL DIALIZERS FOR HEMODIALYSIS IN PATIENTS WITH HIGH RISK FOR BLEEDING - SINGLE CENTRE EXPERIENCE - Pushevski, Vladimir; Canevska, Aleksandra; Sterjova Markovska, Zaklina; Shpishikj Pushevska, Ana Marija; Milenkova, Mimoza; Busletik, Irena Rambabova (Journal of Morphological Sciences, 2023)
During hemodialysis exposure of the blood to the dialysis membrane can promote clotting. So, usually anticoagulation is used. In patients with increased risk for bleeding heparin-free regime is mandatory. Evodial dialyzer contains a heparin-grafted membrane in order to reduce patients' bleeding risk. In this study we are showing our experience with the use of Evodial dialyzer.  We report 106 dialysis sessions in 59 patients were performed. Reasons for using Evodial: active bleeding, hematological conditions, complications of vascular access. Changes in the dialyzer or additional interventions were examined. Low-dose unfractionated heparin was used in 10 (9,4%) sessions, and was added in 6 (5.7%) more and in another 5 ( 4,7%) saline flushing. In 4 (3,8%) sessions due to coagulation we had to terminate dialysis. Heparin-grafted dialyzers can be safely used in patients with high-risk for bleeding as reasonable alternative when regional citrate anticoagulation is unavailable.   K ey words : Evodial, heparin-free dialysis, chronic kidney disease, high-risk for bleeding. https://doi.org/10.55302/JMS2361098p